2015
DOI: 10.4067/s0718-95162015005000075
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neem extract and azadirachtin on soil microorganisms

Abstract: Both neem extract and azadirachtin are widely used in agriculture as organic pesticides because they are nontoxic to humans, animals, and the environment. However, their effects on soil microorganisms and plant growth-promoting rhizobacteria (PGPR), which directly affect soil quality, remain largely unexplored. In this study, the effects of neem extract and azadirachtin on the activity of soil microbes and rhizosphere microorganisms was evaluated. We found that 0.1 and 0.4 gmL -1 of the extract and 1.25 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(16 reference statements)
1
11
0
1
Order By: Relevance
“…Again, in this analysis, Sample [B] performed better than Samples [A] and [C]. This result is similar to the result of the studies [31][32][33] in which Neem extract improved water resistance and dimensional stability of bamboo culms and its products.…”
Section: Water Absorption Testsupporting
confidence: 89%
“…Again, in this analysis, Sample [B] performed better than Samples [A] and [C]. This result is similar to the result of the studies [31][32][33] in which Neem extract improved water resistance and dimensional stability of bamboo culms and its products.…”
Section: Water Absorption Testsupporting
confidence: 89%
“…Administration of leaves extracts (0.1 and 0.4 g/ml) and azadirachtin (1.25 and 2.5 μg/ml) inhibited in vitro activity of soil growth‐promoting rhizobacteria. Two months treatment of soil with azadirachtin reduced number of microorganisms in soil whereas leaves extracts enhanced both soil microorganism and rhizosphere's activities (Sarawaneeyaruk, Krajangsang, & Pringsulaka, ). Growth disrupting effect of seed extracts in water and organic solvents was observed at imaginai stage of Aedes aegypti larval development.…”
Section: Pharmacological Attributesmentioning
confidence: 99%
“…46,47 ACT is a good alternative to conventional insecticides, displaying no resistance problems due to its chemical complexity and nontoxic nature to mammals, beneficial arthropods, and warm-blooded vertebrates. 48 Unfortunately, ACT has a rapid biodegradability, especially in regard to photothermal factors that would accelerate its decomposition, 17,49,50 which greatly limits its application ranges in the agricultural field. Our results indicated that the decomposition rate of ACT after encapsulation in the WPU carrier was much slower than that of free ACT.…”
Section: ■ Results and Discussionmentioning
confidence: 99%